2019
DOI: 10.1002/jat.3791
|View full text |Cite
|
Sign up to set email alerts
|

A microarray‐based comparative analysis of gene expression profiles in thyroid glands in amphibian metamorphosis: differences in effects between chemical exposure and food restriction

Abstract: Tadpoles during metamorphosis are sensitive to chemical exposure as shown in the amphibian metamorphosis assay, which is a method to detect effects of chemicals on the functions of hypothalamus‐pituitary‐thyroid axis. The present study reports existence of different modes of action between pyriproxyfen (PYR) and 6‐propyl‐2‐thiouracil (PTU) under different feeding conditions based on gene expression profiles (transcriptomics) in the thyroid glands of tadpoles of the African clawed frog, Xenopus laevis. PTU and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Histomorphological changes of the thyroid gland are used as a sensitive indicator for chemical‐induced thyrotoxicity (Grim et al 2009; Miyata and Ose 2012). Usually, histopathological changes were characterized by glandular atrophy, reduced colloid, and follicular cell hyperplasia (Zhao et al 2013; Ose et al 2019; Yang et al 2019). Several studies have shown that exposure to Cr (VI) affects thyroid gland histological characteristics in experimental organisms (Hassanin et al 2013; Mishra and Mohanty 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Histomorphological changes of the thyroid gland are used as a sensitive indicator for chemical‐induced thyrotoxicity (Grim et al 2009; Miyata and Ose 2012). Usually, histopathological changes were characterized by glandular atrophy, reduced colloid, and follicular cell hyperplasia (Zhao et al 2013; Ose et al 2019; Yang et al 2019). Several studies have shown that exposure to Cr (VI) affects thyroid gland histological characteristics in experimental organisms (Hassanin et al 2013; Mishra and Mohanty 2015).…”
Section: Discussionmentioning
confidence: 99%